2020
DOI: 10.21037/jtd.2020.02.01
|View full text |Cite
|
Sign up to set email alerts
|

Are the dynamic changes of the aortic root determinant for thrombosis or leaflet degeneration after transcatheter aortic valve replacement?

Abstract: The role of the aortic root is to convert the accumulated elastic energy during systole into kinetic flow energy during diastole, in order to improve blood distribution in the coronary tree. Therefore, the sinuses of Valsalva of the aortic root are not predisposed to accept any bulky material, especially in case of uncrushed solid calcific agglomerates. This concept underlines the differences between surgical aortic valve replacement, in which decalcification is a main part of the procedure, and transcatheter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The aortic root is a dynamic structure consisting of several component parts: the semilunar valve cusps, the ventriculoaortic junction, the sinuses of Valsalva and the sinotubular junction (STJ) [53]. A series of complex and asymmetric deformations during the cardiac cycle and the innate elasticity of the root optimize forward flow and minimize stress on the aortic cusps [54][55][56][57][58][59][60].…”
Section: Dynamic Aortic Root Physiologymentioning
confidence: 99%
“…The aortic root is a dynamic structure consisting of several component parts: the semilunar valve cusps, the ventriculoaortic junction, the sinuses of Valsalva and the sinotubular junction (STJ) [53]. A series of complex and asymmetric deformations during the cardiac cycle and the innate elasticity of the root optimize forward flow and minimize stress on the aortic cusps [54][55][56][57][58][59][60].…”
Section: Dynamic Aortic Root Physiologymentioning
confidence: 99%
“…Previously, a clinical study by Nappi et al has indicated that the dynamic variation of the STJ diameter during the cardiac cycle may play an important role in the risk of leaflet thrombosis and degeneration post- TAVR [14]. The STJ diameter has also been related to coronary obstruction, reporting a low STJ-to-TAVR diameter ratio to be a predictor of left main trunk obstruction [15].…”
Section: Introductionmentioning
confidence: 99%
“…(2) intrinsic limitation of leaflet material. 13 Futuristically, more personalized and customized TAVR valves (size, design, and material) may be the correct answer rather than trying to find a "fit-all" anticoagulation strategy. As the authors mention, the studies on use of mechanical circulatory support devices for cardiogenic shock, acute respiratory distress syndrome (ARDS), and sepsis have shown that extracorporeal membrane oxygenation (ECMO) may have a more beneficial role to play than realized yet.…”
mentioning
confidence: 99%
“…Taking a step back, compared with surgical-AVR, the TAVR valve is increasingly predisposed thrombosis and degeneration due to (1) neo-anatomy (axis of left ventricle outflow tract, annulus, and sinuses of Valsalva) and eccentric distortion over time leading to mechanical stress and fluid-dynamic effects on leaflets and stent; and (2) intrinsic limitation of leaflet material. 13 Futuristically, more personalized and customized TAVR valves (size, design, and material) may be the correct answer rather than trying to find a “fit-all” anticoagulation strategy. As the authors mention, the studies on use of mechanical circulatory support devices for cardiogenic shock, acute respiratory distress syndrome (ARDS), and sepsis have shown that extracorporeal membrane oxygenation (ECMO) may have a more beneficial role to play than realized yet.…”
mentioning
confidence: 99%